1990
DOI: 10.1128/aac.34.9.1707
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi proliferation and differentiation are blocked by topoisomerase II inhibitors

Abstract: Chagas' disease is a parasitic disease that affects more than 20 million individuals in Latin America (12). As yet, prophylaxis of the disease has been limited because of the lack of a vaccine or safe chemotherapy. Trypanosoma cruzi, the causative agent of this disease (4), displays a complex life cycle that involves two intermediary hosts (triatomines and mammals) and three differentiation stages: epimastigotes, which replicate in the insect vector; amastigotes, which replicate in mammalian cells; and the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 21 publications
1
23
1
2
Order By: Relevance
“…Data from the literature have shown that the metacyclogenesis process of T. cruzi could be inhibited by the topoisomerase II inhibitor ofloxacin (Gonzales-Perdomo et al 1990), the antitubulin drug trifluralin (Bogitsh et al 1999), the proteasome inhibitor lactacystin (Cardoso et al 2008), metallo and cysteine-protease inhibitors (Bonaldo et al 1991) or mannose (Barbieri et al 1992). The data from the present paper showed that citral effectively blocked the metacyclogenesis of T. cruzi in vitro.…”
Section: Discussionsupporting
confidence: 49%
“…Data from the literature have shown that the metacyclogenesis process of T. cruzi could be inhibited by the topoisomerase II inhibitor ofloxacin (Gonzales-Perdomo et al 1990), the antitubulin drug trifluralin (Bogitsh et al 1999), the proteasome inhibitor lactacystin (Cardoso et al 2008), metallo and cysteine-protease inhibitors (Bonaldo et al 1991) or mannose (Barbieri et al 1992). The data from the present paper showed that citral effectively blocked the metacyclogenesis of T. cruzi in vitro.…”
Section: Discussionsupporting
confidence: 49%
“…This structure represents a potential target in T. cruzi for different drugs (28,41). Examples of such drugs are topoisomerase inhibitors (18,20), aromatic diamidines and reversed amidines (37,40), and the putrescine analogue 1,4-diamino-2-butanone (25). The SEM analysis revealed that the treatment induced severe morphological changes in trypomastigotes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several inhibitors of bacterial DNA topoisomerase II showed activity against T. cruzi, inhibiting both proliferation and differentiation processes, and causing damage to kinetoplast and/or the nucleus of epimastigotes (Kerschmann et al 1989, Gonzales-Perdomo et al 1990), suggesting that both organelles could be the targets of the drugs. Camptothecin, inhibitor of eukaryotic DNA topoisomerase I, induced cleavage of nuclear and mitochondrial DNA in T. cruzi (Bodley & Shapiro 1995).…”
Section: Dna Topoisomerasesmentioning
confidence: 99%